Social impact assessment in urban development in Malaysia - Nur Syafawaty, Abd Rahman (2009)
This study is about social impact assessment in urban development in Malaysia. In this study, social impact assessment is described and discussed. Social impact assessment is defined as ``the process of identifying the future consequences of a current or proposed action which are related to individuals, organizations and social macro-systems''. In the cities of developing countries, the city's center is grown, so this is where for certain projects; impact on people can be by far the most important consideration. In such cases, a social impact assessment (SIA) is carried out as a part of the process. The study of Social Impact Assessment in Urban Development is been carried out in Malaysia. Questionnaire is distributed to the consultant firm, contractor and also government firm for this study. The objective of this study is to assess the way SIA has been used in the past, to consider how social impact assessment in urban development could be improved and to highlight best practice recommendations and general principals of social impact assessment that are relevant for urban development. As conclusion, social impact assessment is important to the urban development in Malaysia. The Social Impact assessment in Malaysia can be improved to prevent the negative impacts.